Calling the police: theoretical insights and practical implications - David Buil-Gil; Laura Huey (Crime Science)
Abstract Studying whether, why, and how people call the police when they experience or witness a crime is crucial for understanding crime patterns, improving the accuracy of crime data, and shaping effective policing and criminal justice responses. Police-recorded crime statistics rely on public reporting, meaning that unreported crimes contribute to the ‘dark figure of crime’, distorting crime estimates and ultimately affecting practice and policy decisions. Understanding reporting behaviors helps identify and address barriers to reporting, including disparities across population groups and locations. This knowledge is essential for supporting evidence-based policing, improving victim support, and enhancing crime prevention strategies. This special collection comprises nine articles that advance theoretical explanations of crime reporting behavior and examine how calls for service shape demand for police services. The articles explore various aspects of crime reporting, including how perceptions of courts influence reporting behavior, how reporting channels impact victims’ satisfaction with the police, and how neighborhood characteristics such as racial composition, economic conditions, and mental health affect crime reporting propensities. Additionally, the collection contributes to understanding crime reporting behaviors for emerging forms of cyber-enabled crime such as cyberstalking and romance fraud. Finally, it explores spatial and temporal patterns of calls for service and proposes ways to better quantify police demand, enabling more informed management and prioritization of resources.